Answer:
x = 3
y = 0
z = 8
Step-by-step explanation:
a) 3x + 3y - z = 1
b) z = 8
c) -x -3y + 2z = 13
a) 3x + 3y - 8 = 1 (substitution)
a) 3x + 3y = 9
c) - x - 3y + 2(8) = 13 (substitution)
c) -x - 3y + 16 = 13
c) -x - 3y = -3
(3x + 3y = 9) + (-x -3y = -3)
= 2x = 6
x = 3
a) 3(3) + 3y - 8 = 1
9 + 3y - 8 = 1
y = (1 -9 + 8)/3
y = 0
Answer:No
Step-by-step explanation:
Answer:
eeeeeeeeeeeeeeeeeee
Step-by-step explanation:
Answer:
C. 16
Step-by-step explanation:
First of all, these two angles are corresponding angles, which means that they equal each other. So, the equation here would be: 2x+18= 4x-14.
Step 1- Move the variables to one side.
2x+18= 4x-14
-2x -2x
18= 2x-14
Step 2- Add 14 to both sides of the equation.
18= 2x-14
+14 +14
32= 2x
Step 3- Divide 2 to both sides of the equation to isolate the variable.
<u>32</u>=<u> 2x</u>
2 2
x= 16